Age-related changes of adaptive and neuropsychological features in persons with Down Syndrome. - Alessandro Ghezzo; Stefano Salvioli; Maria Caterina Solimando; Alice Palmieri; Chiara Chiostergi; Maria Scurti; Laura Lomartire; Federica Bedetti; Guido Cocchi; Daniela Follo; Emanuela Pipitone; Paolo Rovatti; et al. (PLoS ONE)
Down Syndrome (DS) is characterised by premature aging and an accelerated decline of cognitive functions in the vast majority of cases. As the life expectancy of DS persons is rapidly increasing, this decline is becoming a dramatic health problem. The aim of this study was to thoroughly evaluate a group of 67 non-demented persons with DS of different ages (11 to 66 years), from a neuropsychological, neuropsychiatric and psychomotor point of view in order to evaluate in a cross-sectional study the age-related adaptive and neuropsychological features, and to possibly identify early signs predictive of cognitive decline. The main finding of this study is that both neuropsychological functions and adaptive skills are lower in adult DS persons over 40 years old, compared to younger ones. In particular, language and short memory skills, frontal lobe functions, visuo-spatial abilities and adaptive behaviour appear to be the more affected domains. A growing deficit in verbal comprehension, along with social isolation, loss of interest and greater fatigue in daily tasks, are the main features found in older, non demented DS persons evaluated in our study. It is proposed that these signs can be alarm bells for incipient dementia, and that neuro-cognitive rehabilitation and psycho-pharmacological interventions must start as soon as the fourth decade (or even earlier) in DS persons, i.e. at an age where interventions can have the greatest efficacy.